A Review of Research on Seismic Metamaterials. Issue 4 (9th January 2020) - Mu, Di; Shu, Haisheng; Zhao, Lei; An, Shuowei
Abstract : In recent years, elastic metamaterials inspired from electromagnetic metamaterials have been used to protect buildings during earthquakes, and their effectiveness in seismic wave attenuation has been verified by experiments on the geophysical scale. The development of seismic metamaterials however provides a new approach to seismic engineering. Herein the research progress of seismic metamaterials in terms of geometry, physics, and application is introduced. Low frequency and wide bandgap are the two main areas of interest for seismic metamaterials. Then, the parts of elastic metamaterials which are adapted to the two characteristics of seismic waves and do not attract much attention are addressed. Finally, the problems existing in the current research are summarized, and future research prospects are provided, to improve the research framework of seismic metamaterials and provide effective solutions for seismic engineering. Abstract : To improve the research framework of seismic metamaterials and provide effective solutions for seismic engineering, the research progress of seismic metamaterials and some elastic metamaterials adapted to protecting targets from seismic waves is introduced and the existing problems in previous research and prospects of future research contents are summarized.